2016
DOI: 10.12952/journal.elementa.000092
|View full text |Cite
|
Sign up to set email alerts
|

Beyond yields: Climate change effects on specialty crop quality and agroecological management

Abstract: Climate change is impacting the sustainability of food systems through shifts in natural and human dimensions of agroecosystems that influence farmer livelihoods, consumer choices, and food security. This paper highlights the need for climate studies on specialty crops to focus not only on yields, but also on quality, as well as the ability of agroecological management to buffer climate effects on quality parameters. Crop quality refers to phytonutrient and secondary metabolite profiles and associated health a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 117 publications
3
70
0
Order By: Relevance
“…Whereas food demands are growing due to the increasing world population, crop production and quality have suffered from increasing temperatures and considerable shifts in precipitation patterns (Ahmed & Stepp, ; Porter et al, ; Schauberger et al, ). For example, Lesk, Rowhani, and Ramankutty () showed that droughts and extreme heat events between 1964 and 2007 reduced global cereal production by ca.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas food demands are growing due to the increasing world population, crop production and quality have suffered from increasing temperatures and considerable shifts in precipitation patterns (Ahmed & Stepp, ; Porter et al, ; Schauberger et al, ). For example, Lesk, Rowhani, and Ramankutty () showed that droughts and extreme heat events between 1964 and 2007 reduced global cereal production by ca.…”
Section: Introductionmentioning
confidence: 99%
“…The design and management of sustainable agroecosystems requires shifting from an industrial agriculture paradigm focused on yield, returns, and efficiency maximization to one that aims at jointly enhancing the environmental, social, and economic dimensions of the food system [33][34][35]. In this process, assessing the perceptions, experiences, and priorities underpinning agricultural professionals' decisions is critical to develop alternative extension programs that will facilitate the Indicator subdomains for consultants, the only stakeholder group positively associated with S1, included having experience with no-till practices, adding fertilizer on the basis of soil test results, obtaining farming information from field demonstrations, internet resources, and training workshops ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…A database aggregating known climate relationships for specialty crops would be useful. Ideally, such data would include crucial aspects of crop quality as well as yield (Ahmed and Stepp 2016) for sensitive crops such as wine grapes (Duchene et al 2010). These data could inform qualitative investigations of vulnerability and help parameterize quantitative, process-based simulation models to predict the growth and yield of specialty crops under different conditions.…”
Section: Opportunities For Future Researchmentioning
confidence: 99%